The Practical Model and Evidence of Organic Evolution Opposite to Darwin’s Theory of Natural Selection and Sexual Selection (Human Evolution) - Ahad, Md. Abdul (International Journal of Bio-resource and Stress Management, 2023)
Hybridization (breeding) is practical evidence and a model of Darwin’s theory. But it would be true, if hybridization between two plants or animal species is possible and produced a fertile, reproductively isolated offspring. However, hybridization between two plants or animal species is not possible due to structural, behavioural differences, and seasonal isolations. If imposed, the fertilization fails, if the fertilization is successful, the embryo may abort, or the young may die. If the hybrid is survived up to maturity, it must become sterile. However, a very rare case the hybrids become fertile but those produce so-called varieties /races only; those species that produce fertile hybrids (e.g. Indian cattle Bos indicus and European cattle Bos taurus) must merge into a species.to satisfy the modern definition of species. Moreover, the artificial selection is also a skilled sexual selection, as the breeders choose the fittest, most vigour, and most fertile/productive, beautiful, colourful ornamented organism. But breeders also failed to develop a reproductively isolated species/variety/race by Johnson’s pure line selection, cloning, genetic engineering and mutation breeding. Even, a new species is not evolved by the natural hybridization. Consequently, there is no evidence of evolution of a new species either artificially or naturally. So, recent research claims that sexual selection theory is fundamentally flawed and simply wrong. Hence, evolutionary biologists rejected sexual selection. Thus, sexual selection is opposite to the evolution of humans from the lower animal like a chimpanzee. It is assumed that macroevolution occurs through hybridization; so, such an assumption is not valid.